2015
DOI: 10.12693/aphyspola.127.296
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Diffraction, Mössbauer Spectroscopy, and Magnetoelectric Effect Studies of Multiferroic Bi5Ti3FeO15Ceramics

Abstract: Bi5Ti3FeO15 ceramics belongs to multiferroic class of materials. In this work it was prepared by solidstate sintering method and investigated by X-ray diraction, Mössbauer spectroscopy, and magnetoelectric effect measurements. As it was proved by X-ray diraction studies the single-phase Bi5Ti3FeO15 compound was obtained. The Mössbauer investigations revealed paramagnetic character of the compound at room temperature as well as at 80 K. Magnetoelectric measurements were carried out at room temperature using loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…As proved by XRD, Mössbauer spectroscopy, and magnetic measurements, the Bi 5 Ti 3 FeO 15 Aurivillius compound is a single-phase paramagnetic material within the broad temperature range 2–350 K (our earlier articles [38, 39, 45]). Despite being paramagnetic at room temperature, i.e., in the absence of magnetic long-range order, the sample shows magnetoelectric coupling (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…As proved by XRD, Mössbauer spectroscopy, and magnetic measurements, the Bi 5 Ti 3 FeO 15 Aurivillius compound is a single-phase paramagnetic material within the broad temperature range 2–350 K (our earlier articles [38, 39, 45]). Despite being paramagnetic at room temperature, i.e., in the absence of magnetic long-range order, the sample shows magnetoelectric coupling (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…The results of X-ray diffraction studies for Bi 1 −  x Nd x FeO 3 solid solutions and the Aurivillius Bi 5 Ti 3 FeO 15 compound have been published in our previous works [3739]. It was found that with an increase of Nd content in Bi 1 −  x Nd x FeO 3 solid solutions, within the range of x  = 0.2–0.3, a structural phase transition from rhombohedral to orthorhombic system occurs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At room temperature, the ceramics Bi 5 Ti 3 FeO 15 combines ferroelectric, semiconducting, and antiferromagnetic properties [1][2][3], which make it very attractive material for applications as sensors, actuators, and digital memory elements [4][5][6]. Moreover, the Aurivillius Bi 5 Ti 3 FeO 15 compound offers multiferroic properties, having relatively high magneto-electric coupling coefficient α ME ~ 20 mVcm -1 Oe -1 [7] and being one of the few single-phase multiferroics which are in competition for composite materials, e.g. ferroelectric-ferromagnetic composite PZT-ferrite [8].…”
Section: Introductionmentioning
confidence: 99%